Analisis Sistem Akuntansi Penggajian Dan Pengupahan Dalam Upaya Meningkatkan Sistem Pengendalian Internal: Studi Kasus pada PT Kakada Pratama - Astari, Diana; Marlina, Tri (Jurnal Aplikasi Bisnis Kesatuan, 2022)
The purpose of this study is to find out how the application of the payroll and wage accounting system at PT Kakada Pratama and how the internal control system is implemented, at PT Kakada Pratama. The author conducted research at PT Kakada Pratama, which is located on Jl. Batutulis Gg. Jayatunggal No. 3 RT 04 / RW 03 Batutulis Village, South Bogor District, Bogor City 16133. The results showed that PT Kakada Pratama already has a payroll and wage accounting system, such as the documents used, the records used, related functions, and the procedures used. However, in its application to meet the elements and objectives of its internal control system, it still shows the weaknesses that occurred in PT Kakada Pratama so that it has not run well. This is characterized by the negligence of employees in the absence of fingerprints and barcodes, the absence of supervision of working hours to be compared with the time present as the basis for calculating employee salaries and wages, as well as the existence of function traps or parts in the application of payroll and remuneration at PT Kakada Pratama. Keywords : accounting system, payroll and wage system, internal control system